2016
DOI: 10.1002/ijc.30238
|View full text |Cite
|
Sign up to set email alerts
|

Linear viral load increase of a single HPV‐type in women with multiple HPV infections predicts progression to cervical cancer

Abstract: Persistent high-risk human papillomavirus (HPV) infection is strongly associated with development of high-grade cervical intraepithelial neoplasia or cancer (CIN3+). In single type infections, serial type-specific viral-load measurements predict the natural history of the infection. In infections with multiple HPV-types, the individual type-specific viral-load profile could distinguish progressing HPV-infections from regressing infections. A case-cohort natural history study was established using samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 44 publications
(114 reference statements)
5
34
0
Order By: Relevance
“…Together, these metagenomic characteristics are consistent with the ecological principles of competitive exclusion and carcinogenesis hallmarked by clonal expansion and evolution of transformed cells as illustrated in Fig. 6 [3440]. The distinguishing features of altered diversity and dominance between HPV communities may serve well as a biomarker for disease severity.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Together, these metagenomic characteristics are consistent with the ecological principles of competitive exclusion and carcinogenesis hallmarked by clonal expansion and evolution of transformed cells as illustrated in Fig. 6 [3440]. The distinguishing features of altered diversity and dominance between HPV communities may serve well as a biomarker for disease severity.…”
Section: Discussionsupporting
confidence: 75%
“…6Schematic diagram of evolving virus-host interactions on the cervix. After infection (left), virus-virus (middle) and virus-host (right) interactions based on the principles of competitive exclusion and clonal evolution of cancer are illustrated [3440]. Gause’s law of competitive exclusion states that between two competing species, the species with the slightest advantage will ultimately dominate [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…In an interesting study, HPV viral load was assessed after surgical removal of the cervical tumor, and the researchers found that viral load was associated with disease progression but not with cytology grade or age [20]. However, another study found that viral load was a significant predictor associated with the progression of cervical cancer in patients with multiple infection [11]. In our population, only 8 patients had multiple HPV infection.…”
Section: Discussionmentioning
confidence: 64%
“…In diseases related to viral infections, viral load has been shown to be a promising marker for clinical progression [8,9,10]. Although HPV viral load has been showing great potential in predicting cytology abnormalities [11], many studies have reported conflicting results, which may be attributable to their small sample sizes or their use of different types of detection assays [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, HPV infections remain extremely common. Thus, there remains an urgent need to develop therapeutic HPV vaccines (Depuydt et al, 2016; Stanley, 2016). Cancer immunotherapy has emerged as an alternative, innovative approach that can induce the persistent cell-mediated immunity necessary to retard tumor growth.…”
Section: Introductionmentioning
confidence: 99%